IMPLEMENTASI TEKNOLOGI TEPAT GUNA UNTUK DIGITALISASI SEKOLAH DI SMK BINA MADINA DENPASAR - Ni Putu Linda Santiari; Ida Bagus Ketut Surya Arnawa; Ni Nyoman Supuwiningsih; Luh Putu Ersamiya Ika Jayanthi (Jurusan Informatika, Fakultas Matematika dan Ilmu Pengetahuan Alam, Universitas Udayana, 2026)
This Community Service activity under the Appropriate Technology scheme aims to support digital transformation at SMK Bina Madina Denpasar through the development of a school website as a digital information and promotion medium. Problems faced by partners include the unavailability of an official school website, limited media for conveying information to the public, and low utilization of information technology to support educational services and school promotion. These conditions make school information difficult to access for students, parents, and the wider community, thus hampering efforts to improve the school's image and competitiveness. The activity implementation method uses a participatory and collaborative approach consisting of program socialization, needs analysis, website design, system development, implementation, administrator training, and initial evaluation. The results of the activity show that the official school website with an education domain has been successfully developed and published as a means of conveying information on the school profile, activity news, galleries, and communication services with the public. Training on the use of the administrator page also improves the ability of teachers and school staff to manage website content independently and sustainably. The implementation of this appropriate technology has a positive impact on the effectiveness of information dissemination, increasing school promotion, and strengthening the school's digital identity in supporting the digital transformation of education.